Magnetic Resonance Imaging-Defined Osteoarthritis Features and Anterior Knee Pain in Individuals With, or at Risk for, Knee Osteoarthritis: A Multicenter Study on Osteoarthritis - Macri, Erin M.; Neogi, Tuhina; Jarraya, Mohamed; Guermazi, Ali; Roemer, Frank Wolfgang; Lewis, Cora E.; Torner, James C.; Lynch, John A.; Tolstykh, Irina; Jafarzadeh, S. Reza; Stefanik, Joshua J. (Arthritis & Rheumatism-Arthritis Care & Research, 2022)
Objective The lack of strong association between knee osteoarthritis (OA) structural features and pain continues to perplex researchers and clinicians. Evaluating the patellofemoral joint in addition to the tibiofemoral joint alone has contributed to explaining this structure-pain discordance, hence justifying a more comprehensive evaluation of whole-knee OA and pain. The present study, therefore, was undertaken to evaluate the association between patellofemoral and tibiofemoral OA features with localized anterior knee pain (AKP) using 2 study designs. Methods Using cross-sectional data from the Multicenter Osteoarthritis Study, our first approach was a within-person, knee-matched design in which we identified participants with unilateral AKP. We then assessed magnetic resonance imaging (MRI)-derived OA features (cartilage damage, bone marrow lesions [BMLs], osteophytes, and inflammation) in both knees and evaluated the association of patellofemoral and tibiofemoral OA features to unilateral AKP. In our second approach, MRIs from 1 knee per person were scored, and we evaluated the association of OA features to AKP in participants with AKP and participants with no frequent knee pain. Results Using the first approach (n = 71, 66% women, mean +/- SD age 69 +/- 8 years), lateral patellofemoral osteophytes (odds ratio [OR] 5.0 [95% confidence interval (95% CI) 1.7-14.6]), whole-knee joint effusion-synovitis (OR 4.7 [95% CI 1.3-16.2]), and infrapatellar synovitis (OR 2.8 [95% CI 1.0-7.8]) were associated with AKP. Using the second approach (n = 882, 59% women, mean +/- SD age 69 +/- 7 years), lateral and medial patellofemoral cartilage damage (prevalence ratio [PR] 2.3 [95% CI 1.3-4.0] and PR 1.9 [95% CI 1.1-3.3], respectively) and lateral patellofemoral BMLs (PR 2.6 [95% CI 1.5-4.7]) were associated with AKP. Conclusion Patellofemoral but not tibiofemoral joint OA features and inflammation were associated with AKP.
CRIS-Team WoS Importer:2022-06-17